2015
DOI: 10.1016/j.hoc.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Bladder Cancer

Abstract: SYNOPSIS Many detailed studies of the molecular pathogenesis of bladder cancer have been published during the past three decades, identifying important roles for many of the classic cancer pathways in bladder cancer development. Nonetheless, recent large scale mutational and expression analyses in bladder cancer made possible by next generation sequencing and other new techniques have uncovered multiple genes and pathways important for bladder cancer development, many of which were previously unknown. Genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Moreover, activation of the PI3K-AKT–mTOR pathway is correlated with advanced tumor progression and unfavorable survival outcomes 59. A previous study in the TCGA MIBC patient population revealed that the PI3K-mTOR signaling pathway was commonly altered and may serve as a potential therapeutic target 40. These studies complement the results of the GO and KEGG pathway enrichment analyses that focus mainly on angiogenesis-related genes and pathways.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, activation of the PI3K-AKT–mTOR pathway is correlated with advanced tumor progression and unfavorable survival outcomes 59. A previous study in the TCGA MIBC patient population revealed that the PI3K-mTOR signaling pathway was commonly altered and may serve as a potential therapeutic target 40. These studies complement the results of the GO and KEGG pathway enrichment analyses that focus mainly on angiogenesis-related genes and pathways.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have implicated tumor angiogenesis and angiogenesis-related molecular markers as predictors of BUC prognosis 3639. Moreover, a previous study among TCGA MIBC patients revealed that genes from the ErbB family that were related to angiogenesis were frequently altered 40. Another large-scale transcriptomic data of MIBC patients suggested that basal-like MIBC activated the epidermal growth factor receptor (EGFR) pathway, connected with frequent EGFR gains and EGFR autocrine loop activation; in addition, they demonstrated that basal-like MIBC cell lines were sensitive to anti-EGFR therapy 41.…”
Section: Discussionmentioning
confidence: 99%
“…MIBCs are frequently aneuploid with several chromosomic rearrangements, rendering them genetically unstable [32]. Molecular fingerprint of BC presents alterations in genes from several pathways, mainly mutations in genes of the cell cycle, chromatin regulation, and tyrosine-kinase signaling [32,33].…”
Section: Molecular Subtypes Of Bladder Cancermentioning
confidence: 99%
“…From a biological and clinical standpoint, BC is classified into non-muscle invasive (NMIBC), representing 70% to 80% of BC cases, and muscle invasive bladder cancer (MIBC) [50]. These two entities differ in terms of incidence, gene mutations, morphology, and aggressiveness [51][52][53][54]. Cases of NMIBC are further divided into three risk groups (low, intermediate, high) depending on the risk of recurrence and progression after resection [55,56].…”
Section: Bladder Cancermentioning
confidence: 99%